Single Frequency PPP Using Real-Time Regional Broadcast Corrections via NTRIP for the Australian GDA94 Datum - Huisman, L.; Teunissen, Peter; Hu, C. (2014)
The possibility of Real-Time Precise Point Positioning directly in the Australian GDA94 datum has become possible through the availability of Real-Time Broadcast Corrections (BCs) provided by the IGS Real-Time Pilot-Project. Generation of BCs for the GDA94 datum has some pitfalls which are identified in this contribution. It is shown that it is impossible to obtain identical positioning results using either the BCs in ITRF or BCs in GDA94 due to scale differences between both systems. A new user-friendly RBC-approach is introduced, which deals with the scale-induced biases in the current approach. The user-friendly RBC-approach eliminates the user-need of having to apply the ITRF-to-GDA94 transformation, while still giving correct horizontal PPP positions in GDA94. For users that additionally require precise height information in GDA94 as well, a simple constant height-correction, valid for the complete Australian continent, is all that is needed to obtain the correct full 3D PPP position.